2016
DOI: 10.1002/adfm.201604277
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electrical Properties of Nanocomposites Based on Self‐Assembled Pristine Graphene

Abstract: Thermodynamically-driven exfoliation and self-assembly of pristine graphene sheets is shown to provide thermally and electrically functional polymer composites. The spreading of graphene sheets at a high energy liquid/liquid interface is driven by lowering the overall energy of the system, and provides for the formation of water-in-oil emulsions stabilized by overlapping graphene sheets. Polymerization of the oil phase, followed by removal of the dispersed water phase, produces inexpensive and porous composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 31 publications
(32 reference statements)
2
40
0
Order By: Relevance
“…Previous studies on the thermal conductivity of TIMs indicated that the alignment of thermally conductive fillers can make the best of the extraordinarily high in-plane thermal conductivity of BN, CNT, graphene and graphite, and so on [26][27][28]. Substantial researches have focused on fabricating paper-like composites with high in-plane thermal conductivity and low through-plane thermal conductivity [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the thermal conductivity of TIMs indicated that the alignment of thermally conductive fillers can make the best of the extraordinarily high in-plane thermal conductivity of BN, CNT, graphene and graphite, and so on [26][27][28]. Substantial researches have focused on fabricating paper-like composites with high in-plane thermal conductivity and low through-plane thermal conductivity [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, polymer composites using graphene derivatives as filler have been studied with the aim of practical application in a wide range of academic and industrial fields [ 1 , 2 , 3 , 4 , 5 ]. In addition to their superior mechanical and electrical properties, because of the advantage of easily granting suitable physical and chemical characteristics for specific purposes, utilizing them as materials with excellent future prospects has been attracting much attention [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, graphene as a filler component has a tendency to readily aggregate, and this becomes a major disadvantage in that it is difficult to conjugate its inherently excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to inherent 2D structure, high electrical/thermal conductivity, and superstrong mechanical properties along basal plane, the promising applications of graphene are anticipated as a macroscopic thin film for coatings, composites, flexible electrodes, sensors, and so on . Currently, the preparation of graphene thin film relies principally on chemical vapor deposition growth on metal surface, followed by transferring it onto desired substrate .…”
mentioning
confidence: 99%